Gender discrimination and depressive symptoms among child-bearing women: ELSPAC-CZ cohort study - Stepanikova, Irena; Acharya, Sanjeev; Abdalla, Safa; Baker, Elizabeth; Klanova, Jana; Darmstadt, Gary L. (EClinicalMedicine, 2020)
Depression is approximately two-fold more prevalent among women than men. Social theories suggest that discrimination is a pathway through which gender inequalities affect women's lives, but data are lacking. This cohort study evaluates whether perceived gender discrimination is linked to depressive symptoms among child-bearing women. Data were obtained from 4,688 participants enrolled in pregnancy in 1991–92 in the European Longitudinal Cohort Study of Pregnancy and Childhood, Czech Republic. Perceived gender discrimination was assessed in mid-pregnancy, year seven, and year eleven. Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale at eight time-points between mid-pregnancy and year eleven post-delivery. Linear mixed error-component models of depressive symptoms were estimated. Perceived gender discrimination, reported by 10.7% of women, was related to higher depressive symptoms, both in the unadjusted analysis (b = 0.15 [95% confidence interval (CI): 0.12, 0.19], p < 0.001) and in the fully adjusted model (b = 0.12 [95% CI: 0.09, 0.16], p < 0.001). Covariates linked to higher depressive symptoms included financial hardship (b = 0.12 [95% CI: 0.10, 0.14], p < 0.001), childhood emotional/physical neglect (b = 0.18 [95% CI: 0.14, 0.22], p < 0.001), and childhood sexual abuse (b = 0.04 [95% CI: 0.03, 0.06], p < 0.001); an inverse relationship was evident for social support (−0.05 [95% CI: −0.07, −0.04], p < 0.001) and having a partner who performs female-stereotypical household tasks (b=−0.03 [95% CI: −0.05, −0.01], p = 0.001). The findings provide the first evidence that perceived gender discrimination is associated with depressive symptoms among child-bearing women. Social intervention programs aimed at reducing gender discrimination can potentially contribute to better mental health of women. Bill and Melinda Gates Foundation.